121k views
4 votes
The proof for the product property of logarithms requires simplifying the expression logb(bx+y) to x + y. Which property is used to justify this step?

User Kylotan
by
4.3k points

2 Answers

1 vote

Answer:

c. on edge

Explanation:

User Hande
by
5.4k points
4 votes

Answer:


log_bb^c=c

Explanation:

We are given that


log_bb^(x+y)=x+y

We have to find the property which is used to justify this step.

We know that


e^(x+y)=e^x\cdot e^y}

Using the formula


log_b(b^x\cdot b^y)}=log_bb^x+log_bb^y

By using the formula


log(m\cdot n)=log m+log n


log_bb^(x+y)=x+y

By using the property


log_bb^c=c

User Harry Bloom
by
5.2k points